Neurological and neuropsychiatric manifestations of post-COVID-19 condition in South America: a systematic review of the literature - Luisa Pereira de Oliveira Zanetti Gomes; Camila Marinelli Martins; Elis Carolina Pacheco; Letícia Simeoni Avais; Pollyanna Kássia de Oliveira Borges (Arquivos de Neuro-Psiquiatria)
Background The post-COVID-19 condition is a major modern challenge in medicine and has a high global impact on the health of the population.